1980
DOI: 10.3171/jns.1980.52.5.0611
|View full text |Cite
|
Sign up to set email alerts
|

Neurological course and correlated computerized tomography findings after severe closed head injury

Abstract: This study includes 124 patients with closed head injuries and with Glasgow Coma Scale (GCS) scores of less than or equal to 8, who were admitted over a 7 1/2-month period. The time at which death occurred after injury was bimodal: deaths occurred either within 48 hours or after 7 days or longer after injury. Neurological deterioration, however, occurred with equal frequency on Days 2 to 7 after injury. Patients who survived the first 48 hours and then suffered neurological deterioration did not differ from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(44 citation statements)
references
References 24 publications
0
42
0
2
Order By: Relevance
“…The time at which death occurs after an injury is bimodal, with 70% of all deaths occurring in the first 48 hours. 6,7 A hospital-based study revealed that 28% of the patients died during the first day of hospitalization. 28 In our cohort of TBI patients, the mortality within 48 hours was 22%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time at which death occurs after an injury is bimodal, with 70% of all deaths occurring in the first 48 hours. 6,7 A hospital-based study revealed that 28% of the patients died during the first day of hospitalization. 28 In our cohort of TBI patients, the mortality within 48 hours was 22%.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,16,36,37,39,42 Few studies have analyzed the characteristics of patients who succumbed to early death after a TBI. 2,[6][7][8] The first aim of this study was to derive a prognostic model for early death (within 48 hours) to be used within the first 6 hours after a severe TBI and to externally validate this model. The second aim was to develop a clinical prediction rule based on the previous model to identify those patients who would be most likely to die early.…”
mentioning
confidence: 99%
“…4) Spontaneous resolution of signs of herniation due to SDH (mainly ASDH) within 24 hours is extremely rare and may be related to a rapid decrease in intracranial pressure. 2) The signs of herniation in our patient observed on admission resolved within only 6 hours. Only eight of the many case reports on the disappearance and diminution of ASDH described the resolution of signs of herniation 1,8,10,11,15) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Delayed traumatic intracerebral hematoma is a serious complication with a high mortality of from 30 to 72% reported for various series [2,3, [12][13][14][15]. Delayed diagnosis and treatment is a common cause of this high mortality [3], although the severity of the initial impact and secondary insults are also contributory [15].…”
Section: Discussionmentioning
confidence: 99%
“…Focal brain injury is thought to result in decreased vascular resistance, allowing an increased head of arterial pressure and increased blood flow to be transmitted to an already traumatized capillary-vascular bed, with resultant hemorrhage into the cerebral parenchyma [2, 7,13,16]. Compression of the brain caused by a hematoma or edema can produce ischemia, necrosis, and secondary hemorrhage [12]. Mechanical distortion producing ischemia and infarction may cause delayed traumatic intracerebral hematoma [17].…”
Section: Discussionmentioning
confidence: 99%